KAJIAN RASIO TINGKAT KESEJAHTERAAN MASYARAKAT PULAU TASIPI DENGAN PULAU TIGA KABUPATEN MUNA - Nurdiana Azis; Roslindah Daeng Siang (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2015)
This study aims to identify the characteristics community of the Tasipi Island and Tiga Island by affecting the well-being, then find out how big the difference of the level welfare between Tasipi Island and Island Tiga in the District of North Tiworo Muna. The research method was used survey method with data collection techniques of direct observation, and interviews with the help of a questionnaire. The population is homogeneous for each island so random sampling technique. The results showed tha